2020
DOI: 10.1029/2020gl087091
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Aridity and Apparent Soil Moisture Drought in European Forest During Heat Waves

Abstract: Land‐atmosphere feedbacks, in particular the response of land evaporation to vapor pressure deficit (VPD) or the dryness of the air, remain poorly understood. Here we investigate the VPD response by analysis of a large database of eddy covariance flux observations and simulations using a conceptual model of the atmospheric boundary layer. Data analysis reveals that under high VPD and corresponding high temperatures, forest in particular reduces evaporation and emits more sensible heat. In contrast, grass incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 39 publications
2
28
2
2
Order By: Relevance
“…This drying occurs despite the potential suppressing effect of stomatal closure at higher VPD (Massmann et al, 2019; Medlyn et al, 2011). This result is consistent with previous findings that transpiration increases with VPD in many species, even if stomatal resistance increases (Cunningham, 2004; Lansu et al, 2020; Monteith, 1995; Mott & Parkhurst, 1991; Teuling et al, 2010; Urban et al, 2017). Additionally, greater soil temperatures are associated with higher conductance and transpiration (Cochard et al, 2000).…”
Section: Resultssupporting
confidence: 93%
“…This drying occurs despite the potential suppressing effect of stomatal closure at higher VPD (Massmann et al, 2019; Medlyn et al, 2011). This result is consistent with previous findings that transpiration increases with VPD in many species, even if stomatal resistance increases (Cunningham, 2004; Lansu et al, 2020; Monteith, 1995; Mott & Parkhurst, 1991; Teuling et al, 2010; Urban et al, 2017). Additionally, greater soil temperatures are associated with higher conductance and transpiration (Cochard et al, 2000).…”
Section: Resultssupporting
confidence: 93%
“…Though urban forests can provide enhanced cooling benefits (e.g. Gunawardena et al , 2017), recent studies showed increasing emission of latent heat in grassland rather than forest during drought conditions in Europe (Lansu et al , 2020). While such large-scale findings may not be easily transferable to plot-scale, urban site, isotope tracers in our study revealed higher soil evaporation under urban grassland, though tree transpiration and interception lead to similarly high ET rates over the growing season.…”
Section: Wider Implicationscontrasting
confidence: 77%
“…This has provided valuable insight into the timing and impact of drought on GPP (Sippel et al, 2018;Stocker et al, 2019). Several studies have shown that spatio-temporal patterns of GPP are correlated with solar-induced chlorophyll fluorescence (SIF), a satellite product which measures the reemission of light by chloroplasts during photosynthesis (Frankenberg et al, 2011;Koren et al, 2018;Li et al, 2018). Badgley et al (2017Badgley et al ( , 2019 found that SIF correlates strongly with satellite-obtained near-infrared reflectance of terrestrial vegetation (NIRv) and proposes to use this as a proxy for GPP.…”
Section: Introductionmentioning
confidence: 99%